FACTORS INFLUENCING STUDENTS’ CHOICES AND DECISION- -MAKING PROCESS: A CASE STUDY OF POLISH STUDENTS STUDYING IN A BRITISH HIGHER EDUCATION INSTITUTION - Rembielak, Grażyna; Rashid, Tahir; Parlińska, Agnieszka (Acta Scientiarum Polonorum. Oeconomia, 2020)
The main aim of this paper is to investigate the factors which influence students when deciding to study abroad. The case study is based on Polish students studying in the British higher education system (UK HE) and the paper examines these students’ choices and their decision-making process when selecting their university studies. The literature review suggests that there are two types of factors influencing students’ decision- making process: push factors, which operate within the home country, and pull factors, meaning that students are attracted by the host country and encouraged to study there. Polish students constitute a significant group of EU students who study in the UK and yet there are very few studies on this particular group. The results from this qualitative research on Polish students studying in a selected British university indicate that, contrary to a number of other studies, pull factors could be more important in influencing Polish students’ decision-making process regarding studying abroad.